Impact of psychological factors on the final clinical outcomes of patients undergoing ankle arthrodesis and ankle replacement - Wang, Hongze; Cao, Shihang; Liu, Geng; Lu, Jun; Xu, Junkui (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to analyze the impact of different surgical procedures on the prognosis and psychological state of patients with end-stage ankle arthritis (ESAA) by comparing two groups of patients with ESAA who have undergone total ankle replacement (TAR) and ankle arthrodesis (AA), and to investigate whether preoperative psychological status can alter the final clinical outcomes.MethodsThis study retrospectively collected data from 66 patients with ESAA who underwent AA surgery in the Foot and Ankle Surgery Department of Xi’an Honghui Hospital between 2016 and 2023. In July 2024, the final follow-up of patients was conducted via telephone or WeChat, with a follow-up duration of no less than 12 months. Before surgery and at the final follow-up, evaluations were conducted using the Chinese version of the Hospital Anxiety and Depression Scale (HADS), the Visual Analogue Scale (VAS) for pain (ranging from 0 to 100mm), and the American Orthopaedic Foot and Ankle Society (AOFAS) ankle and hindfoot score. The study compared differences in pain scores, functional scores, and psychological scores between patients in the TAR and AA groups before surgery and at the final follow-up. Additionally, patients who underwent TAR and AA were further subgrouped based on the severity of their preoperative psychological status, in order to analyze the impact of preoperative psychological conditions on surgical prognosis.ResultsA total of 66 patients with ESAA completed the follow-up. At the final follow-up, both the VAS and AOFAS scores in the TAR group and the AA group showed significant improvement compared to preoperative levels. Among them, the TAR group performed better in terms of AOFAS scores, but no significant difference was observed in VAS scores between the two groups. Additionally, there was no significant difference in HADS scores between the two groups at the final follow-up. Regardless of whether they belonged to the high-HADS group or the low-HADS group, patients showed significant improvement in clinical scores compared to preoperative levels. However, at the final follow-up, the clinical scores of the high-HADS group were significantly lower than those of the low-HADS group, and the incidence of complications in the high-HADS group was also higher.ConclusionThis study found that both TAR and AA significantly improved patients’ psychology, pain, and functional activities. Both surgical methods demonstrated similar improvements in terms of final psychological status and pain relief. However, patients in the TAR group showed better ankle function and mobility. Patients with poorer preoperative psychological status had worse clinical outcomes and faced a higher risk of complications. The study indicates that both TAR and AA are effective treatment options for patients with ESAA, but poor preoperative psychological status is one of the important risk factors for poor prognosis. Therefore, when selecting a treatment approach, the patient’s psychological state and needs should be fully considered, and necessary psychological interventions and postoperative rehabilitation plans should be implemented to enhance the patient’s treatment outcomes and quality of life.